2023
DOI: 10.1038/s41467-023-36595-w
|View full text |Cite
|
Sign up to set email alerts
|

Nsun2 coupling with RoRγt shapes the fate of Th17 cells and promotes colitis

Abstract: T helper 17 (Th17) cells are a subset of CD4+ T helper cells involved in the inflammatory response in autoimmunity. Th17 cells secrete Th17 specific cytokines, such as IL-17A and IL17-F, which are governed by the master transcription factor RoRγt. However, the epigenetic mechanism regulating Th17 cell function is still not fully understood. Here, we reveal that deletion of RNA 5-methylcytosine (m5C) methyltransferase Nsun2 in mouse CD4+ T cells specifically inhibits Th17 cell differentiation and alleviates Th1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…Interestingly, we wondered why the decrease in mRNA m 5 C modification was correlated with a decrease in gene expression. Recent studies have shown that modifications to transcripts can affect their stability [ 33 36 ]. Specifically, certain RNA-binding proteins (RBPs) can recognize and bind to these modification sites, thereby affecting their translation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we wondered why the decrease in mRNA m 5 C modification was correlated with a decrease in gene expression. Recent studies have shown that modifications to transcripts can affect their stability [ 33 36 ]. Specifically, certain RNA-binding proteins (RBPs) can recognize and bind to these modification sites, thereby affecting their translation.…”
Section: Resultsmentioning
confidence: 99%
“…After the staining procedure, the data were acquired with the MACSQuant Analyzer 10 from Miltenyi Biotec and processed using the FlowJo software (v10.5.3). In this study, CD4 + IL-17A + cells are denoted as Th17 60 and CD4 + Foxp3 + cells are denoted as Treg. 61 …”
Section: Methodsmentioning
confidence: 99%
“…NSUN2通过催化IL-17A mRNA C466的m 5 C修饰, 促进了IL-17A在T淋巴细胞中的翻 译, 介导高同型半胱氨酸血症(hyperhomocysteinemia, HHcy)诱导T淋巴细胞活化 [149] . Nsun2与RoRγt偶联, 特异性催化Th17细胞关键细胞因子mRNA m 5 C修饰 的形成, 增强其靶基因的稳定性, 诱导肠炎发生 [150] .…”
Section: 在食管鳞状细胞癌样本中 转录因子E2f1可调控unclassified